2022
DOI: 10.1001/jamasurg.2022.2770
|View full text |Cite
|
Sign up to set email alerts
|

Excluding Hollow Viscus Injury for Abdominal Seat Belt Sign Using Computed Tomography

Abstract: Abdominal seat belt sign (SBS) has historically entailed admission and observation because of the diagnostic limitations of computed tomography (CT) imaging and high rates of hollow viscus injury (HVI). Recent single-institution, observational studies have questioned the utility of this practice.OBJECTIVE To evaluate whether a negative CT scan can safely predict the absence of HVI in the setting of an abdominal SBS. DESIGN, SETTING, AND PARTICIPANTSThis prospective, observational cohort study was conducted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Importantly, this study is not about whether imaging is superior to the physical examination. It is about how to use a valuable tool to its maximum capacity.…”
supporting
confidence: 51%
See 2 more Smart Citations
“…Importantly, this study is not about whether imaging is superior to the physical examination. It is about how to use a valuable tool to its maximum capacity.…”
supporting
confidence: 51%
“…In this issue of JAMA Surgery , Delaplain and colleagues deserve high praise for their efforts to improve trauma care by incorporating current imaging technology. Three single-center studies from the last 5 years found minimal, if any, association between SBS and hollow viscus injury in patients with blunt trauma if the CT scan on admission to the emergency department is negative.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this prospective observational study, 754 patients from nine US trauma centres with blunt abdominal injury and an abdominal seat belt sign (ASBS) underwent high resolution and multislice CT 3. The primary outcome was hollow viscus injury at operative intervention, which was found in in 9.2% of patients.…”
Section: Excluding Hollow Viscus Injury For Abdominal Seat Belt Sign ...mentioning
confidence: 99%